Visual Perception from a Computer Graphics Perspective - Thompson, William; Fleming, Roland; Creem-Regehr, Sarah; Stefanucci, Jeanine Kelly (A K Peters/CRC Press, 2016)
This book provides an introduction to human visual perception suitable for readers studying or working in the fields of computer graphics and visualization, cognitive science, and visual neuroscience. It focuses on how computer graphics images are generated, rather than solely on the organization of the visual system itself; therefore, the text pro.
Keywords: Computer graphics -- Design; Vision; Visual perception; Vision, Ocular; Visual Perception; Perception visuelle; sight (sense); visual perception; Computer graphics; Design; Livres numériques